1988
DOI: 10.1111/j.1432-1033.1988.tb13983.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine‐proteinase‐inhibiting function of T kininogen and of its proteolytic fragments

Abstract: Previous attempts to liberate T kinin from T kininogen Eur. J. Biochem. 15Y, 341 -346;Gutman et al. (1988) Eur. J. Biochem. 171, have shown that complete fragmentation of the precursor molecule into inhibitory peptides was achieved before any vasoactive peptide was released, suggesting a possible physiological significance for this phenomenon. In this study, cysteine-proteinase-inhibiting properties of rat T kininogen and of its proteolytic fragments issuing from trypsin and submaxillary gland endopeptidase k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 31 publications
(5 reference statements)
0
17
0
Order By: Relevance
“…Rat liver cathepsin B was purified as previously described [17]. Recombinant human cathepsin B was a gift from Dr. John S. Mort (McGill University, Montreal, Canada).…”
Section: Enzymesmentioning
confidence: 99%
“…Rat liver cathepsin B was purified as previously described [17]. Recombinant human cathepsin B was a gift from Dr. John S. Mort (McGill University, Montreal, Canada).…”
Section: Enzymesmentioning
confidence: 99%
“…The recombinant catalytic domain of cruzipain was a gift from Dr. James McKerrow (University of California, San Francisco, CA). Cathepsins B and L were purified from rat liver (32). The activation buffers for enzyme assays were 0.1 M phosphate buffer, pH 6.0, containing 6 mM DTT and 2 mM EDTA for congopain, and 0.1 M phosphate buffer, pH 6.0, containing 10 mM DTT for cruzipain, 0.1 M phosphate buffer, pH 6.0, containing 1 mM EDTA, 2 mM DTT for cathepsins B and L. Titration of the active site was made using E64 (33).…”
mentioning
confidence: 99%
“…Rat mast cell chymase was purified by the procedure of Kido et al [27] and rat liver cathepsin L as reported in [23]. Papain was purchased from Boehringer Mannheim.…”
Section: Enzymesmentioning
confidence: 99%
“…Plasma was obtained from turpentine-injected Wistar rats and used to prepare thiostatin as described previously [23].…”
Section: Biological Materialsmentioning
confidence: 99%